Macular Ganglion Cell Layer Thickness after Macula-Off Rhegmatogenous Retinal Detachment Repair: Scleral Buckling versus Pars Plana Vitrectomy - Gharbiya, Magda (J Clin Med, 2020)
(1) Background: We evaluated macular ganglion cell layer–inner plexiform layer (GCL-IPL) thickness in patients with primary macula-off rhegmatogenous retinal detachment (RRD) treated with scleral buckling (SB) or pars plana vitrectomy (PPV) using spectral domain optical coherence tomography (SD-OCT). (2) Methods: In this retrospective, observational study, we reviewed the medical records of patients undergoing SB or PPV surgery for macula-off RRD. SD-OCT was performed at three and 12 months after surgery. The central and parafoveal GCL-IPL thicknesses in treated eyes were compared with those of healthy fellow eyes. OCT measurements between the SB and PPV group were also compared using the analysis of covariance. (3) Results: Seventy-one eyes of 71 patients with a mean age of 61.2 ± 11.7 years were included. The parafoveal GCL-IPL thickness of the PPV group was significantly reduced, with respect to fellow eyes, at three and 12 months (p < 0.01). After adjusting for age, axial length, spherical equivalent, RD extent, preoperative intraretinal cysts, duration of symptoms and postoperative IOP, the parafoveal GCL-IPL thickness in the PPV group was significantly reduced with respect to the SB group, both at three and 12 months (F = 11.45, p = 0.001 and F = 12.37, p = 0.001, respectively). (4) Conclusions: In conclusion, the GCL-IPL is reduced in thickness in eyes with macula-off RRD treated with vitrectomy and is significantly thinner compared to eyes undergoing scleral buckling surgery.